Sodobni vidiki zdravljenja stenoze aortne zaklopke pri starostnikih - Dolenc, Jure (Medicinski razgledi, 2007)
Degenerative aortic stenosis is the second commonest heart valve disorder in the adult population in the developed world. The basic pathologic process is aortic valve sclerosis. The incidence and prevalence of degenerative aortic valve stenosis is increasing because of the ageing of the population. The treatment of aortic stenosis is traditionally surgical regardless of the patient's age. Indications for valve replacement are the same for the elderly as for other patients. Because of frequent comorbidities and worse general health of the elderly, operative mortality is greater in this subgroup of patients. Until recently, it was believed that drug treatment is ineffective, and without surgery 50% of symptomatic patients die within 3 years. However, percutaneous aortic bioprosthesis implantation is a possible new treatment modality. This is not a routine procedure yet and is undertaken in exceptionalcases in inoperable elderly patients. The latest discoveries in thepathogenesis of aortic stenosis did not answer the question of whether disease progression can be delayed or halted with drugs.
Keywords: Aortic Valve Stenosis; Aortna zaklopka, stenoza; Ehokardiografija; Surgery; Srce, zaklopka, proteza; Heart Valve Prosthesis; Echocardiography; Starostniki; Aged; aortna stenoza; srce; heart